2005
DOI: 10.1002/cyto.a.20143
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of calibration beads for sorting cells expressing a β‐lactamase gene reporter

Abstract: Background: Modern drug discovery has been based on high-throughput screening using whole-cell assays. A prominent role has been assigned to the reporter gene technology based on a b-lactamase and the fluorogenic substrate CCF2. Successful application of this technology requires fluorescence-activated cell sorting. We describe the preparation and characterization of calibration beads for sorting cells expressing the b-lactamase gene using the CCF2 substrate. Methods: To model F€ orster resonance energy transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Overall, only 50.7% (3482/6866) of background repressors are considered cytotoxic based on the Cell Titer Glo viability screen. While, multiple cytotoxicity and cell viability screens can be used together to capture different pathways and markers of cytotoxicity, a review of BLA assay-development literature suggested that BLA activity may decrease background fluorescence by converting green cells to blue without affecting the cell number. As BLA breaks down CCF2/4, coumarin concentration increases, and the cell changes color from green to blue. , The change in color corresponds to increase in 460 nm fluorescence and may lead to decreased background fluorescence because fewer cells are now green, while the total number of cells remains constant. , Thus, strong BLA upregulation is expected to turn many cells blue and may decrease fluorescence at 530 nm without cytotoxicity. Indeed, 67.6% of chemicals that induce channel 2 response with E MAX above 50% of positive control activity and AC 50 below −4.5 log 10 M units repress background activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, only 50.7% (3482/6866) of background repressors are considered cytotoxic based on the Cell Titer Glo viability screen. While, multiple cytotoxicity and cell viability screens can be used together to capture different pathways and markers of cytotoxicity, a review of BLA assay-development literature suggested that BLA activity may decrease background fluorescence by converting green cells to blue without affecting the cell number. As BLA breaks down CCF2/4, coumarin concentration increases, and the cell changes color from green to blue. , The change in color corresponds to increase in 460 nm fluorescence and may lead to decreased background fluorescence because fewer cells are now green, while the total number of cells remains constant. , Thus, strong BLA upregulation is expected to turn many cells blue and may decrease fluorescence at 530 nm without cytotoxicity. Indeed, 67.6% of chemicals that induce channel 2 response with E MAX above 50% of positive control activity and AC 50 below −4.5 log 10 M units repress background activity.…”
Section: Resultsmentioning
confidence: 99%
“…40−42 As BLA breaks down CCF2/4, coumarin concentration increases, and the cell changes color from green to blue. 40,41 The change in color corresponds to increase in 460 nm fluorescence and may lead to decreased background fluorescence because fewer cells are now green, while the total number of cells remains constant. 40,41 Thus, strong BLA upregulation is expected to turn many cells blue and may decrease fluorescence at 530 nm without cytotoxicity.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assay could be used to specifically image endogenous cell-surface furin, urokinase plasminogen activator metallo-protease activity. Cunnningham et al explained that polystyrene beads could be successfully utilized for establishing fluorescent-activated cell sorting to sort cells with the Bla reporter gene by using the substrate CCF2 (Cunningham et al, 2005). Lippard demonstrated the efficient screening over 3600 reaction products of platinum based antitumor drugs for their ability to inhibit transcription of Bla in the BlaM HeLa cell line by monitoring the cleavage of CCF2/AM.…”
Section: β-Lactamase (Bla)mentioning
confidence: 99%